Rapid land-use change and its impacts on tropical biodiversity - Laurance, William F. (Geophysical Monograph Series, 2004)
Rates of forest conversion are extremely high in most tropical regions and these changes are known to have important impacts on biotas and ecosystems. I summarize available information on responses of wildlife and plant communities to habitat fragmentation, selective logging, surface fires, and hunting, which are four of the most widespread types of tropical land-use change. These changes alter forest ecosystems in complex ways and have varying impacts on different animal and plant species. In most human-dominated landscapes, forests are subjected to not one change but to two or more simultaneous alterations, the effects of which can be particularly destructive to tropical biotas. I illustrate this concept by describing the synergistic interactions between habitat fragmentation and surface fires, and between logging, fires, and hunting. © 2004 by the American Geophysical Union.